172k views
3 votes
What is the simplified form of

of (-7xº+5x²-x+6)-(-8x2 + x +3)?
ОА.
-x + 4x2 - x+3
OBX + 4x² - x+3
ocx - 4x² – 2-3
D. -15x + 6x? - X+9
Please I need help immediately

User FerCa
by
5.8k points

1 Answer

10 votes

Note: Your answer choices remain a little unclear. But, I have solved the concept and solution, so you can easily figure it out.

Answer:


\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)=13x^2-2x-4

Explanation:

Given the expression


\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)

solving the expression


=-7x^0+5x^2-x+6-\left(-8x^2+x+3\right)

apply the rule:
a^0=1,\:a\\e \:0


=-7+5x^2-x+6-\left(-8x^2+x+3\right)


=-7+5x^2-x+6+8x^2-x-3

simplify


=13x^2-2x-4

Therefore, the simplified form is:


\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)=13x^2-2x-4

Note: Your answer choices remain a little unclear. But, I have solved the concept and solution, so you can easily figure it out.

User Abinash
by
6.0k points